Biostimulants application effects on the quality and antioxidant capacity of zucchini fruits (Cucurbita pepo L. var. ‘Grey Zucchini’) - Soriano-Melgar, Lluvia de Abril Alexandra; Izquierdo-Oviedo, Humberto; Saucedo-Espinosa, Yvette Alessandra; Cárdenas-Flores, Antonio (REVISTA TERRA LATINOAMERICANA, 2020)
Nowadays, agricultural research has not been only focused on studying the effect of different treatments on plant development and yield, but it has also been involved on study their effect on the postharvest quality of products. This study was conducted to determine the treatment effect based on plant growth-promoting rhizobacteria (Azotobacter chroococcum), alone or combined with different oligosaccharins of pectic origin (Pectimorf®) or derivatives of chitosan (Quitomax®), on the postharvest quality of zucchini fruits (Cucurbita pepo L.) var. 'Grey Zucchini'. Physical characteristics (polar and equatorial diameter, weight, dry biomass, f irmness, and color) and chemical characteristics (pH, total soluble solids, treatable acidity and vitamin C), proteins, antioxidant enzymatic activities (superoxide dismutase, catalase and total peroxidase), polyphenol oxidase activity, and antioxidant content (phenolic compounds and antioxidant capacity) were evaluated. Results showed significant differences (P ≤ 0.05) between control and treatments in most of the parameters evaluated, such as: color, length (up to 15.88%), width (up to 16.25%), weight (up to 57.31%), dry biomass (up to 34.43%), pH (down to 9.72%), vitamin C (up to 162.6%) and protein content (up to 22.38%), and total antioxidant capacity (down to 18.72%). Therefore, plant treatments improved the quality and composition of postharvest fruits, which accentuates the importance of organic treatments during the development of plants to obtain fruits with better organoleptic characteristics.